2018
DOI: 10.1096/fj.201700994r
|View full text |Cite|
|
Sign up to set email alerts
|

Translationally controlled tumor protein is required for the fast growth of Toxoplasma gondii and maintenance of its intracellular development

Abstract: Translationally controlled tumor protein (TCTP) is a highly conserved, multifunctional protein that has been implicated in a range of cell physiologic processes, especially cell growth and development. A TCTP-like gene has been identified in the Toxoplasma genome [ Toxoplasma gondii TCTP ( TgTCTP)], although its function remains unknown. The sequence analysis of TgTCTP indicated that it is a highly conserved protein in eukaryotes. We found that the expression level of TgTCTP in the virulent RH strain was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Translationally controlled tumor protein is ubiquitously expressed, highly conserved protein present in various type of cells and tissues implicating its essential role in normal cells. This conservation is also observed in the protozoans, such as Plasmodium, Toxoplasma, and Dictyostelium (Bhisutthibhan et al, 1998;Zheng et al, 2018). It is involved in regulation of cell cycle, development, cytoskeleton, autophagy, and apoptosis.…”
Section: Discussionmentioning
confidence: 80%
“…Translationally controlled tumor protein is ubiquitously expressed, highly conserved protein present in various type of cells and tissues implicating its essential role in normal cells. This conservation is also observed in the protozoans, such as Plasmodium, Toxoplasma, and Dictyostelium (Bhisutthibhan et al, 1998;Zheng et al, 2018). It is involved in regulation of cell cycle, development, cytoskeleton, autophagy, and apoptosis.…”
Section: Discussionmentioning
confidence: 80%
“…Since the completion of our Special Issue, a few interesting biological activities of TCTP have been reported in non-vertebrate organisms. Some examples are its role in the growth, development and differentiation of the slime mold Dictyostelium discoideum [ 21 ]; the importance in Drosophila for epithelial integrity and organ growth [ 22 ]; and in Toxoplasma gondii for robust growth of the parasite and for the maintenance of its virulence [ 23 ]. Recognizing the importance of TCTP for the survival of unicellular parasites, Bossard et al [ 24 ] took the step to test the efficacy of immunizing mice against the parasitic TCTP of Trypanosoma brucei .…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Particularly in human parasites, little is currently known about the functions and processes that involve TCTP orthologs, but some studies have shown that they collaborate in parasite growth, proliferation, reproduction and response to stress conditions, which is why this protein has been suggested as a possible therapeutic target [3][4][5]. Toxoplasma gondii has been reported to require its TCTP ortholog for rapid growth and to maintain its intracellular development [3].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in human parasites, little is currently known about the functions and processes that involve TCTP orthologs, but some studies have shown that they collaborate in parasite growth, proliferation, reproduction and response to stress conditions, which is why this protein has been suggested as a possible therapeutic target [3][4][5]. Toxoplasma gondii has been reported to require its TCTP ortholog for rapid growth and to maintain its intracellular development [3]. Moreover, TCTP has been shown to act as an antioxidant and heat shock protein with chaperone activity in some parasites [6][7][8] and can also interact and sequester antiparasitic drugs, thus contributing to the development of resistant strains [9][10][11].…”
Section: Introductionmentioning
confidence: 99%